EKSPLORASI DAN KARAKTERISASI PLASMA NUTFAH KACANG-KACANGAN MINOR DI KABUPATEN MALUKU TENGGARA BARAT - Helen Hetharie; S. H.T. Raharjo; M. L. Hehanussa; J. D. Siwalette; E. Jambormias (Zuriat, 2011)
Germplasms of food crops with a high diversity can be found in Maluku Tenggara Barat (MTB) District, include plant legumes. The objectives of this research were: (1) to find minor legume species with a high diversity based on their morphology, (2) to determine diversity centers of the minor legumes in Maluku Tenggara Barat District.  This research used a survey method, with determination of sample subdistricts, villages and farmers by a purposive sampling.  Four subdistricts, i.e. Wertamrian, Kromomolin, Selaru and Tanimbar Utara, with 8 sample villages, were selected. Morphological characterizations were based on the descriptor guides.  The data were analyzed qualitatively, in the forms of figures. The research results showed that there were six minor legume species cultivated in MTB, those were kacang tunggak [Vigna unguiculata (L.) Walp], kacang koro karatok (Phaseolus lanatus L.), kacang gude [Cajanus cajan (L.) Millsp], kacang komak (Lablab purpureus L. Sweet), kacang uci (Vigna umbellata) and kacang kecipir (Psophocarpus tetragonolobus), with a diversity center in Selaru Subdistrict. The highest within-species diversity based on seed color and shape was found in Vigna unguiculata with 14 accessions, with a center in Tanimbar Utara Subdistrict. Within-species diversities in Phaseolus lanatus with eight accessions, followed by Cajanus cajan with six accessions, were found with a diversity center in Selaru Subdistrict.